A conversion strategy on photo-response bifunctional motor enriched with oxygen vacancies enable lignin depolymerization. (March 2023) - Xiao, X.; Han, Y.; Liu, C.; Li, Y.; Sun, G.; Wang, X.
Abstract: Overconsumption of fossil energy is mitigated by conversion of lignin to higher value products in the pulp and paper industry, where the breakage of the β-O-4 linkages plays a prominent role as the core technology. Herein, a photo-response motor (Au–H–TiO2 ) using water as fuel was prepared by using the one-step solvent volatilization method to break the β-O-4 linkages in lignin models under visible light irradiation. The Au–H–TiO2 with microscopic morphology of H-doped surface oxygen-deficient TiO2 microspheres semi-encapsulated by Au layers exploits the liquid flow difference formed by the proton elimination reaction occurring on the TiO2 hemispherical surface encapsulated by Au layers (Au hemispherical surface) as the power source of driving photocatalysis. Structural and spectroscopic analyses confirm that the abundant oxygen vacancies possess the ability to prolong the separation time of photogenerated carriers on the TiO2 hemispherical surface not encapsulated by Au layers (TiO2 hemispherical surface) and achieve an efficient visible light response by building a new band gap within the forbidden band. Simultaneously, the oxygen vacancies on the Au hemispherical surface act as photoelectron trapping sites to accelerate the movement rate of Au–H–TiO2 by promoting the elimination of protons. Notably, Au–H–TiO2 fueled by visible light and water can drive the synergistic vibration of the lignin models to ensure its uniform dispersion in water and complete the breakage of the β-O-4 linkages of the lignin models within 240 min without external mechanical assistance. Herein, it is predicted that high-value utilization of lignin using solar radiation as a single influencing factor has a promising research value. Graphical abstract: Image 1 Highlight: Modulation of oxygen defects on the surface of TiO2 microspheres without impurity introduction. Bifunctionalization of oxygen vacancies in Au–H–TiO2 : promote carrier separation and enhance photoelectron trapping. Oxygen vacancy-assisted Au–H–TiO2 drives the free movement of lignin models under visible light.